Pengaruh Promosi Big Sale dan Gratis Ongkos Kirim Shopee Terhadap Minat Beli Anak Muda di Kabupaten Tanggamus - Wiliardi lexi leyley; Wahyu Cahyo Pratama; Vicky F Sanjaya (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2022)
The purpose of this study was to determine how influential the promotion of big sale and free shopee shipping costs on the buying interest of young people in Tanggamus district, with young people using yhe shopee application as the object of this study. The method used in this study using a questionnaire method. The sample of this study amounted to 71 respondents. Statistical tests were carried out using Cronbach’s alpha, composite reliability, and Average Variance Extracted (AVE). All proposed hypotheses are supported and significant. The conclusion of this study is the Big Sale Promotion, and Free Shipping Shopee have a significant positive effect on the Buying Interest of young people in Tanggamus Regency.